Artificial Riboswitches Methods and Protocols - Ogawa, Atsushi; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Artificial riboswitches and other ligand-responsive gene regulators make it possible to switch protein synthesis ON or OFF with arbitrary ligand molecules. Artificial Riboswitches: Methods and Protocols focuses on the state-of-the-art methods developed in recent years for creating artificial riboswitches, therefore this volume could be regarded as a collection of recipes for the gene circuit elements in synthetic biology and metabolic engineering. Chapters cover topics such as screening or rational design methods for obtaining artificial riboswitches that function in either bacterial or eukaryotic translational systems, protocols for evaluating the activities of the resultant riboswitches, as well as protocols for construction of ligand-dependent, trans-acting gene regulators. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Artificial Riboswitches: Methods and Protocols seeks to serve not only bioengineers who aim to reprogram cell behaviors and molecular biologists who leverage these regulators for genetic studies, but to all researchers interested in this fascinating field.
Computational Design of RNA Libraries for in vitro Selection of Aptamers -- In vitro Selection of RNA Aptamers for a Small-Molecule Dye -- Development of Photoswitchable RNA Aptamer-Ligand Complexes -- Identification of RNA Aptamers Against Recombinant Proteins with a Hexa-Histidine Tag -- Artificial Riboswitch Selection: A FACS-Based Approach -- FRET-Based Optical Assay for Selection of Artificial Riboswitches -- Portable Two-Way Riboswitches: Design and Engineering -- Generation of Orthogonally Selective Bacterial Riboswitches By Targeted Mutagenesis and in vivo Screening -- Dual Genetic Selection of Synthetic Riboswitches in Escherichia coli -- Nucleotide Kinase-Based Selection System for Genetic Switches -- Measuring Riboswitch Activity in vitro and in Artificial Cells with Purified Transcription-Translation Machinery -- Rational Design of Artificial ON-Riboswitches -- Engineering Protein-Responsive mRNA Switch in Mammalian Cells -- Guanine-Tethered Antisense Oligonucleotides as Synthetic Riboregulators -- In Vitro Selection of Allosteric Ribozymes that Sense the Bacterial Second Messenger c-di-GMP -- Dual-Selection for Evolution of in vivo Functional Aptazymes as Riboswitch Parts -- In vivo Screening for Aptazyme-Based Bacterial Riboswitches -- Engineered Riboswitch as Gene-Regulatory Platform for Reducing Antibiotic Resistance -- Construction of Ligand-Responsive microRNAs that Operate Through Inhibition of Drosha Processing -- A Three-Dimensional Design Strategy for a Protein-Responsive shRNA Switch.
Keywords: Biochemistry; Biochemical engineering; Biochemistry, general; Biochemical Engineering